Efektivitas Peranan Pemerintah Dalam Meningkatkan Jumlah Kunjungan Wisata Di Taman Nasional Bantimurung Kabupaten Maros - Abdul Sahid; Ambo Masse (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Maros is one of the districst that has interesting tourist attractions known as waterfalls, so that for the sake of sustainability the role of the local government of Maros regency is needed. This type of research uses a qualitative approach, with a sample of 15 people consisting of employees, officers, and the community. Base on the results of the research, it showns that the government’s role as a regulator is always balancing, between the wishes of tourists and tourist objects in bantimurung Nasional Park. A side from being a regulator, the government is also a facilitator, motivator, and dynamicator.